Analisis Pengukuran Konsumsi Energi Pada Media Sosial Menggunakan Sensor Arus - Harold Situmorang; Priyulida, Fitria (Universitas Sari Mutiara Indonesia, 2023)
In the world of mobile communication, current measurement is still done manually so it takes time and cost to process. Making this research aims to design automatic detection tools based on the social media used. This tool uses Arduino Mega2560 components and a current sensor as the main tool that functions as a sensor to measure power and energy. Based on the testing of the tool, the time used. It can be concluded that the designed tool can work optimally automatically displaying measurement results.